Analysis of Moral Value in the Picture Story of the Fable Edition “Our Tax” by the Directorate Of Extension, Services, and Public Relations - Rianti; Septiana Pradyta; Trisnawati Hutagalung; Fania Nurtriana, Fania Nurtriana (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2022)
The purpose of this study is to describe the moral values ​​contained in the fable book